Design and Control of A Standalone Photovoltaic Power System For Telecommunications In Isolated Regions of Algeria - Hamza, Sahraoui; Moussa Mohamed, Ali; Mellah, Hacene; Maafa, Amar; Yahiou, Abdelghani; Taieb, Bessad; Mechnane, Farouk; Kamal, Baazouzi; Said, Drid; Chrifi-Alaou, Larbi (IAES Indonesian Section, 2026)
In this paper, we describe the design, control, and management of a photovoltaic (PV) power supply system for a remote telecommunications facility situated in Bab Ezzouar, Algiers, Algeria, that maintains Base Transceiver Stations (BTS) in remote areas where the intermittent grid is either unavailable or non-existent. The proposal is developed and modeled in MATLAB/Simulink for a freestanding PV-battery hybrid system that utilizes a DC-DC boost converter regulated by a Perturb and Observe (P&O) Maximum Power Point Tracking (MPPT) algorithm. The proposed system endeavour’s to maximize solar energy harvesting while maintaining a constant energy supply for remotely situated telecommunication BTS without grid connection in a variety of environmental conditions. The simulation results indicate effective MPPT and battery charge-discharge management performance, ensuring BTS autonomy and serviceability 24/7, while demonstrating both technical feasibility and operational efficiency associated with the use of PV-based systems to meet the energy needs of isolated telecommunication infrastructure in North African regions, which have considerable solar potential.